2014
DOI: 10.1007/s11748-014-0404-z
|View full text |Cite
|
Sign up to set email alerts
|

Right axillary arterial perfusion for descending thoracic or thoracoabdominal aortic aneurysm repair with open proximal anastomosis through left thoracotomy

Abstract: Right axillary perfusion facilitates easy evacuation of air and allows prompt recommencement of upper body circulation. Consequently, it minimizes the risk of cerebral embolism or complications in relation to aortic cannulation through left thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Kawaharada et al reported the incidence rate of cerebral embolism as 3.4% in DTA or TAA repair under deep hypothermic CA for a mean duration of 28 min, and advocated the use of right axillary arterial perfusion. 13) In comparison, our patient cohort had a higher incidence of PND (6.7%). However, it is noteworthy that the mean duration of SCP for our …”
Section: Discussionmentioning
confidence: 62%
“…Kawaharada et al reported the incidence rate of cerebral embolism as 3.4% in DTA or TAA repair under deep hypothermic CA for a mean duration of 28 min, and advocated the use of right axillary arterial perfusion. 13) In comparison, our patient cohort had a higher incidence of PND (6.7%). However, it is noteworthy that the mean duration of SCP for our …”
Section: Discussionmentioning
confidence: 62%
“…However, it is a very invasive surgical procedure, with reported hospital mortality and stroke rates of 3%–10% and 3%–11%, respectively. 1,2,4,9,11,12 Furthermore, if the distal arch or proximal descending aorta has aneurysmal or atherosclerotic changes or dissection, aortic crossclamping may cause vascular injury or stroke. Although open proximal anastomosis with HCA can be performed to prevent such complications, it is an invasive procedure.…”
Section: Discussionmentioning
confidence: 99%
“…After exposing the aortic aneurysm, extracorporeal circulation was established. Previously, arterial flow was returned through the right axillary and femoral arteries, 9 but we have recently started using the left axillary and femoral arteries. Venous inflow to the extracorporeal circuit was obtained from the femoral vein.…”
Section: Methodsmentioning
confidence: 99%
“…Shiiya et al reported using antegrade perfusion by transapical aortic cannulation to prevent debris scattering due to retrograde perfusion from the femoral artery in a patient undergoing thoracoabdominal aortic repair by left thoracotomy [ 7 ], and Takemura et al reported the usefulness of transapical cannulation in preventing malperfusion during a deep hypothermic procedure to repair an acute traumatic descending aortic rupture [ 10 ]. Although antegrade perfusion via the axillary artery is safe and possible [ 11 ], it is difficult to ensure the visual field during a left thoracotomy procedure.…”
Section: Discussionmentioning
confidence: 99%